Long-term dynamics of forage base and food supply for nekton in the upper epipelagic layer of the western Bering Sea. Part 2. Food supply for nekton - S. V. Naydenko; A. A. Somov (Известия ТИНРО, 2022)
Interannual dynamics of feeding conditions for nekton in the upper epipelagic layer of the western Bering Sea is considered for the summer and fall seasons of 2002–2020. In the summers, daily consumption by fish and squids ranged from 0.01 to 0.10 t/km2 in the deepwater basins and between 0.01–0.38 t/km2 in the shelf area at Cape Navarin. In the falls, the consumption increased to 0.03–0.14 t/km2 in the deep-water basins, and to 0.01–0.53 t/km2 in the Navarin area. Summary in the summer-fall periods, the fish and squids consumed 2–5 % of zooplankton production (up to 5–7 % in some years) in the deep-sea basins that is rather low degree of the zooplankton resources usage. In the Navarin area, the consumption is considerably higher and is estimated as 5 % in summer and 21 % in fall season, on average. In cases of heightened nekton biomass and reduced zooplankton biomass in some years, the grazing pressure on plankton increased, in particular on euphausiids, hyperiids and pteropods, while the intensity of salmon feeding decreased, with extension the portions of nektonic food and other zooplankton groups, as arrowworms, in their diet. On the other hand, the portion of juvenile fish and squids in the salmon diet increased in cases of high abundance of this prey, too. Weak correlation was detected both between the salmon feeding and abundance of their prey and between the salmon feeding and abundance of salmons. The feeding conditions for pink salmon during their offshore migration did not determine the rate of their returns. Strong year-classes of pink salmon had large returns in conditions of either poor or rich food supply in fall season, so the feeding in fall was not important for the pink salmon survival in the ocean in winter. Feeding of other fish and squids species did not change noticeably in the years with reduced food supply. In general, abundance and species composition of plankton and nekton communities were rather stable in the western Bering Sea in the 2000-2010s, and this current state of the ecosystem provides stable functioning of nekton communities both in the deepwater and Navarin areas.